Smart Leather Using Thermoresponsive Cholesteric Liquid Crystals in Surface Finishing - Cosmin-Andrei Alexe; Carmen Gaidau; Ioana Rodica Stanculescu; Cristina Burducea; Viorel Cîrcu (Journal of Natural Fibers, 2025)
Leather is the oldest collagen-based fibrous material with outstanding natural properties in footwear, clothes, bags or upholstery fabrication. In the competition between natural and synthetic products, intelligent surface properties bring added value to the former and create high tech materials. The chromatic transition properties responsive to various external stimuli have become not only of great aesthetic value but also a first step toward smart sensor functions, for thermal, pressure or environmental toxicity warning. Cholesteric liquid crystals represent materials with such properties, which, however, are difficult to transfer to flexible surfaces, such as natural leather. The paper presents the progress recorded in achieving thermochromic properties on leather surface with the help of a mixture of cholesteric liquid crystals dispersed in a polymer by applying an original process. The characteristics of the CLC films dispersed in polymers and the leathers covered with these films were evaluated by optical microscopy, TGA, DSC, SEM, AFM and FTIR techniques and a uniform distribution of CLC and smoother surface were identified. The evaluation of resistance properties of the finish indicates very good values for the water drop test and dry and wet rubbing. Antimicrobial protection properties have been identified as an advantage of these new coatings.